Holocene relief and soil changes in loess-covered areas of south-western Germany: The pedosedimentary archives of Bretten-Bauerbach (Kraichgau) - Kadereit, Annette; Kühn, Peter; Wagner, Günther A. (Quaternary international, 2010)
Based on infrared-stimulated luminescence (IRSL) dating of loess-borne sediments, a chronometry of Holocene landscape evolution is established for a representative study site in the early settled Kraichgau area in south-western Germany. The results show that the gently rolling relief is due essentially to soil erosion and colluvial deposition triggered by humans cultivating the loess soils since the onset of agriculture in the Neolithic period. Levelling of relief is accompanied by alterations in soil-type patterns from Haplic Luvisols before the impact of humans, over variably truncated Luvisols with Bt-horizons prevailing at the slope surfaces in the Middle Ages, to Calcaric Regosols characterizing both sites of erosion and accumulation since then. The tremendous changes show that the effects of human activities have been recorded over thousands of years, indicating an early Anthropocene in a geomorphological and pedological sense. Most landscapes are probably more modified by humans than thought at first sight. As the results show, this recognition requires considering that current geomorphological and soil forming processes might work at different frequencies or magnitudes (e.g. by changes of internal system thresholds, such as increased erodibility following the complete erosion of a more resistant Bt-horizon) and/or in a different direction (e.g. accumulation instead of erosion or sediment transport due to slope angles decreased by former deposition of colluvium) than they would in the absence of a human-controlled pre-history.